Rebalancing the euro area: Is wage adjustment in Germany the answer?. (December 2021) - Hoffmann, Mathias; Kliem, Martin; Krause, Michael; Moyen, Stéphane; Šauer, Radek
Highlights: Evaluating the impact of wage inflation on the trade balance. Using an estimated 3-country DSGE model. Monetary policy and constant interest rates amplify the transmission. Wage inflation unlikely to reduce imbalances by a quantitatively meaningful amount. Abstract: We assess the extent to which wage inflation policies in Germany could contribute to an economic rebalancing in the euro area and the rest of the world. We find that a rise in nominal wage inflation has positive short-run effects on inflation and output in Germany and the rest of the euro area. The duration of constant interest rates and expectations about the monetary policy stance matter to the magnitude of the results obtained. We establish that the modeling of the trade relationships with the rest of the world is of particular importance, as it allows us to capture the induced relative price movements and hence changes in competitiveness within the three regions. Our results are obtained from an estimated DSGE model which consists of Germany, the rest of the euro area, and the rest of the world.